2016
DOI: 10.1002/hed.24569
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral vocal fold paralysis and dysphagia secondary to diffuse idiopathic skeletal hyperostosis

Abstract: In the case presented, cervical osteophytectomy dramatically reversed bilateral vocal fold paralysis and dysphagia secondary to hyperostosis, thus negating the need for prolonged tracheostomy and feeding tube dependence. © 2016 Wiley Periodicals, Inc. Head Neck 39: E1-E3, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Furthermore a chondritis could occur with subsequent involvement of the arytenoids and ankylosis of the cricoarytenoid joint, which is likely to be the reason why the vocal cord immobilisation of our patient did not improve ( 8 ). Another possible reason could be an infection of the recurrent nerve itself ( 10 , 19 ). We could exclude this in our patient because the intraoperative electromyography of the vocal muscle on both sides showed normal action potentials ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore a chondritis could occur with subsequent involvement of the arytenoids and ankylosis of the cricoarytenoid joint, which is likely to be the reason why the vocal cord immobilisation of our patient did not improve ( 8 ). Another possible reason could be an infection of the recurrent nerve itself ( 10 , 19 ). We could exclude this in our patient because the intraoperative electromyography of the vocal muscle on both sides showed normal action potentials ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Combinations of dysphagia and respiratory distress are observed less frequently and it may be due to the excessive ossifications or more extensive compressions that develop. [32][33][34][35][36][37][38][39] If the corresponding osteophyte is larger on one side it may result in a distortion of the upper aero-digestive corridors with an accompanying aggravation of the preexisting symptoms. [32][33][34][35][36][37][38][39] Respiratory discomfort develops in a faster and more prominent fashion when a distortion is present 32 Retrocricoid inflammation may also induce laryngeal edema, dysphonia, vocal cord immobility, and stridor.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39] If the corresponding osteophyte is larger on one side it may result in a distortion of the upper aero-digestive corridors with an accompanying aggravation of the preexisting symptoms. [32][33][34][35][36][37][38][39] Respiratory discomfort develops in a faster and more prominent fashion when a distortion is present 32 Retrocricoid inflammation may also induce laryngeal edema, dysphonia, vocal cord immobility, and stridor. [30][31][32][33][34][35][36][37][38][39] With an impingement of the esophagus, it is rare to observe the concomitant compression of the recurrent laryngeal nerve on the left side that is secondary to spiky spur formations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can include tracheostomy and gastric tube placement for nutritional support or osteophytectomy which is considered to be highly successful when conservative methods fail [ 22 , 23 ]. Several authors have reported cases of dysphagia including one with bilateral vocal fold paralysis secondary to DISH where tracheotomy and cervical osteophytectomy have successfully been performed, reporting marked improvement in swallowing function and speaking ability [ 14 , 23 25 ]. However, recognizing the limited data regarding this condition, studies assessing the efficacy of both strategies to treat dysphagia and/or airway obstruction in the presence of DISH are lacking.…”
Section: Discussionmentioning
confidence: 99%